(untitled) (Global Journal of Management and Business Research, 2018)
Nowadays the population data of countries as Japan, India, China, United States and Mexico, at glance seem to evolving over time according to a logistic pattern. In this context arises the following research question: will there be any form to prove the hypothesis of the logistic pattern? But this question implies three questions more, is there exist a minimum and a maximum for population growth? Will be able to be the values of the maximum and minimum determined numerically? And how can this information be used to projecting the population? In order to answer above questions we use the Stable Bounded Theory. The data we used in this paper were elaborated by National Institute of Statistic and Geography from Mexico and they cover last 225 years. Key results of the paper indicate that; first, in Mexico the assumption about the logistic pattern is true, second, minimum value for population growth of Mexican population is 7.1 million, while maximum is 153.6; and third, using the minimum and maximum values estimated and the Logistic pattern we forecasted M#xE9;xico#xB4;s population, so that, in 2020 will be 125.18 million, in 2030 will be 134.51 million, for 2040 will be 141.1, and in 2050 will it arrive to 145.56.